Antecedent Drought Condition Affects Responses of Plant Physiology and Growth to Drought and Post-drought Recovery - Li, Ximeng; Bao, Jingting; Wang, Jin; Blackman, Chris; Tissue, David (Frontiers in Forests and Global Change, 2021)
Antecedent environmental conditions may have a substantial impact on plant response to drought and recovery dynamics. Saplings of Eucalyptus camaldulensis were exposed to a range of long-term water deficit pre-treatments (antecedent conditions) designed to reduce carbon assimilation to approximately 50 (A50) and 10% (A10) of maximum photosynthesis of well-watered plants (A100). Thereafter, water was withheld from all plants to generate three different levels of water stress before re-watering. Our objective was to assess the role of antecedent water limitations in plant physiology and growth recovery from mild to severe drought stress. Antecedent water limitations led to increased soluble sugar content and depletion of starch in leaves of A50 and A10 trees, but there was no significant change in total non-structural carbohydrate concentration (NSC; soluble sugar and starch), relative to A100 plants. Following re-watering, A50 and A10 trees exhibited faster recovery of physiological processes (e.g., photosynthesis and stomatal conductance) than A100 plants. Nonetheless, trees exposed to the greatest water stress (−5.0 MPa) were slowest to fully recover photosynthesis (Amax) and stomatal conductance (gs). Moreover, post-drought recovery of photosynthesis was primarily limited by gs, but was facilitated by biochemistry (Vcmax and Jmax). During recovery, slow regrowth rates in A50 and A10 trees may result from insufficient carbon reserves as well as impaired hydraulic transport induced by the antecedent water limitations, which was dependent on the intensity of drought stress. Therefore, our findings suggest that antecedent water stress conditions, as well as drought severity, are important determinants of physiological recovery following drought release.